Deposit Insurance in Malaysia: Shariah Perspective and Muslims Acknowledgement - Nor Haziah Hashim; Syahidawati Hj. Shahwan (Universiti Sains Islam Malaysia, 2024)
Deposit insurance is an insurance system established by policy makers in many countries to protect depositors against the loss of their deposits which are placed in bank(s) in the event of a 'run' on a bank. The United States was the first country to establish an official deposit insurance scheme during the Great Depression banking crisis in 1934, during which large number of customers of a bank withdrew their deposits because they feared it might become insolvent. In Malaysia, the system was launched on September 2005, and administered by the Malaysia Deposit Insurance Corporation (MDIC). This article will discuss the concept and historical aspect of deposit insurance and also the operation of Malaysia Deposit Insurance Corporation (MDIC). In addition to that, this article also discusses the Shariah perspective on this measure. A short survey was also administered to determine the public awareness and understanding of the scheme.